2009
DOI: 10.1128/aem.00274-09
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Bacterial Community Structure in Streams Affected by Acid Mine Drainage

Abstract: We examined the bacterial communities of epilithic biofilms in 17 streams which represented a gradient ranging from relatively pristine streams to streams highly impacted by acid mine drainage (AMD). A combination of automated ribosomal intergenic spacer analysis with multivariate analysis and ordination provided a sensitive, high-throughput method to monitor the impact of AMD on stream bacterial communities. Significant differences in community structure were detected among neutral to alkaline (pH 6.7 to 8.3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 35 publications
(23 reference statements)
3
45
2
Order By: Relevance
“…pH also controls the aqueous speciation of Fe-SO 4 complexes that impact ferrihydrite or schwertmannite precipitation, which can impair cellular transport processes and impact the availability of Fe 2ϩ to microbial cells (52). Multiple studies have noted the role of pH in partially explaining microbial community distribution in AMD (13)(14)(15). Interestingly, in a study of pilot scale iron oxidation bioreactors, a shift from Ferrovum-to Gallionella-dominated communities occurred with a slight increase in pH (to just above 3) and a slight decrease in Fe 3ϩ during the late stages of operation of one reactor (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pH also controls the aqueous speciation of Fe-SO 4 complexes that impact ferrihydrite or schwertmannite precipitation, which can impair cellular transport processes and impact the availability of Fe 2ϩ to microbial cells (52). Multiple studies have noted the role of pH in partially explaining microbial community distribution in AMD (13)(14)(15). Interestingly, in a study of pilot scale iron oxidation bioreactors, a shift from Ferrovum-to Gallionella-dominated communities occurred with a slight increase in pH (to just above 3) and a slight decrease in Fe 3ϩ during the late stages of operation of one reactor (46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent analysis of 59 AMD sites in China found that pH was the most important explanatory variable across all sites (15). However, many taxa co-occur in similar pH ranges, and other studies have found that environmental factors, including dissolved oxygen, conductivity, temperature, and iron and other metal concentrations are also important controls on microbial community composition (14)(15)(16)(17)(18)(19)(20). In addition to contemporary environmental selection, microbial populations may also be affected by geographic isolation, which can maintain microbial communities independent of contemporary environmental factors by preserving the influence of past environmental factors or the history of stochastic microbial colonization (19,21).…”
mentioning
confidence: 99%
“…S7), which suggests that this phylum has a cosmopolitan distribution, although typically found at low relative abundance. Its ecological distribution (derived from published and unpublished studies that have deposited related sequences in GenBank) includes domestic water sources (17,39,45), acidic cave biofilms, acid mine drainage biofilms (46), wastewater biofilms (47), soil, contaminated groundwater and subsurface sites (48,49), aquatic moss, hypersaline mats, peat bogs, and peat swamps (30,50). These and additional environments where TM6 was detected in 16S rRNA gene clone libraries, including a number of biofilm-related samples, are highlighted in SI Appendix, Table S1.…”
Section: Phylogenetic and Phylogenomic Analyses Of Candidate Phylum Tm6mentioning
confidence: 99%
“…Biofilms are often considered problematic from the human perspective owing to the damage associated with their presence (rusting, dental plaque formation, and the disease cystic fibrosis) (8). The focus of the present study is on microbial biofilms that are instrumental in the generation of acid mine drainage (AMD) (1,10,16,20,32). The deleterious environmental effects of AMD necessitate research to characterize biofilm structure in such systems, which could provide insight into treatment approaches and environmental control.…”
mentioning
confidence: 99%